Wound closure and alveoplasty after preventive tooth extractions in patients with antiresorptive intake: a randomized pilot trial - Ristow, Oliver; Rückschloß, Thomas; Moratin, Julius; Müller, Michael; Kühle, Reinald; Horn, Dominik; Pilz, Maximilian; Shavlokhova, Veronika; Otto, Sven; Hoffmann, Jürgen; Freudlsperger, Christian (Oral diseases, 2021)
Objectives - To compare success rates between the sub-periosteal prepared (SPP) muco-periosteal flap and the epi-periosteal prepared (EPP) mucosa flap and the feasibility of alveoplasty after surgical tooth extractions in patients undergoing/after antiresorptive treatment.
Bei der Angabe des sechsten Verfassers sind Vor- und Nachname vertauscht
First published: 17 July 2020
Gesehen am 17.12.2021